2019
DOI: 10.1093/beheco/arz169
|View full text |Cite
|
Sign up to set email alerts
|

High and dry: Trade-off in arboreal calling in a treefrog mediated by local environment

Abstract: Trade-offs shaping behavioral variation are often influenced by the environment. We investigated the role that the environment plays in mediating trade-offs using a widespread frog with a conspicuous mating display, Pseudacris crucifer. We first demonstrated, using playback and desiccation experiments, that calling site selection involves a trade-off between sound transmission and desiccation. We then determined the influence of local environmental conditions on the intensity of the trade-off by examining rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…In other frog species, arboreal habitat use is often associated with mating behaviours (Kime et al 2000). Calls transmitted from arboreal perches can travel farther than those made at ground level making them detectable to a greater number of potential mates (Parris 2002;Cicchino et al 2020). However, leiopelmatid frogs lack external ears and do not produce mating calls.…”
Section: Discussionmentioning
confidence: 99%
“…In other frog species, arboreal habitat use is often associated with mating behaviours (Kime et al 2000). Calls transmitted from arboreal perches can travel farther than those made at ground level making them detectable to a greater number of potential mates (Parris 2002;Cicchino et al 2020). However, leiopelmatid frogs lack external ears and do not produce mating calls.…”
Section: Discussionmentioning
confidence: 99%
“…We extend this argument here, and propose that the frequency differences we found in our analyses are mainly caused by different constraints on sound production imposed by aquatic and nonaquatic calling sites. Furthermore, calling sites differ not only in the biomechanical constraints they impose, but also in other factors such as exposure to desiccation or temperature (Camurugi et al., 2015; Cicchino et al., 2020). This suggests that other call variables, such as some temperature‐dependent temporal patterns, may also be impacted by calling site choice.…”
Section: Discussionmentioning
confidence: 99%
“…The association between size and frequency is a well-described physical consequence of vocal sound production, and it is suggested that ecological factors driving changes in body size also have concomitant effects on signal frequency (Wilkins et al, 2013). A similar case of morphology-driven signal evolution can be found in Darwin finches, where diet-dependent changes in beak morphology are accompanied by modification in song production (Podos, 2001;Podos & Nowicki, 2004 (Cicchino et al, 2020;Mathevon et al, 1996;Schwartz et al, 2016). Variation in body size will not only have a direct impact on call frequency due to allometry, but may also limit the possible calling sites a species can occupy, highlighting the relevance of the interaction between morphology and calling site on signal evolution.…”
Section: Phylogenetic Path Analysismentioning
confidence: 92%
“…Interspecific body size variation in frogs is related to the utilization of different calling posts, such as aquatic and non-aquatic sites (Muñoz et al 2020), and also to environmental factors relevant for heat and water balance (Amado et al 2019). For example, male spring pepper frogs ( Pseudacris crucifer ) calling from above the ground are larger and their calls propagate further, but experience a six-fold increase in desiccation rate relative to frogs calling near the ground (Cicchino et al 2020). Therefore, display sites associated with contrasting environmental conditions can impact body size evolution, and therefore also modify the frequency of vocalizations.…”
Section: Discussionmentioning
confidence: 99%